2016
DOI: 10.3758/s13414-016-1255-8
|View full text |Cite
|
Sign up to set email alerts
|

Free hand proprioception is well calibrated to verbal estimates of slanted surfaces

Abstract: We investigate the relationship between verbal and hand proprioception of slant. In Experiment 1 we demonstrate that verbally estimating free hand orientation produces overestimates by a factor of 1.67. These values are similar to those seen for verbal overestimates of slanted surfaces. In Experiment 2, participants positioned their hand to a ramp at 1 of 4 different orientations, and then verbally estimated the orientation of either their hand or the ramp. We show that verbal estimates of the ramp are a produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(36 reference statements)
1
0
1
Order By: Relevance
“…Additionally, across the conditions of Experiment 1, verbal estimations of positioned and drawn orientations of the most stable position for a ladder to be leaned against a wall and verbal (conceptual) estimates of the most stable position at which to position a ladder were all shallower than the actual orientation of positioned or drawn ladders (i.e., lines representing ladder orientation). This is counter to most previous work showing that there is a perceptual scale expansion of geographic and manmade hills, roads, ramps, and people's own orientation, leading to steeper verbal estimates (Durgin & Li, 2011;Proffitt et al, 1995;Shaffer & Taylor, 2017;.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Additionally, across the conditions of Experiment 1, verbal estimations of positioned and drawn orientations of the most stable position for a ladder to be leaned against a wall and verbal (conceptual) estimates of the most stable position at which to position a ladder were all shallower than the actual orientation of positioned or drawn ladders (i.e., lines representing ladder orientation). This is counter to most previous work showing that there is a perceptual scale expansion of geographic and manmade hills, roads, ramps, and people's own orientation, leading to steeper verbal estimates (Durgin & Li, 2011;Proffitt et al, 1995;Shaffer & Taylor, 2017;.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings from Experiment 1 showed that people are pretty accurate at placing a ladder at the most stable position, erring on the side of placing the ladder slightly too shallow, as had been found in previous work (Häkkinen, Pesonen, & Rajamäki, 1988;Irvine & Vejvoda, 1977). This also fits the results of palm board and forearm tasks for near surfaces , in which gains are~1, and also with manmade and geographical slants when there is no anchoring (e.g., Shaffer, McManama, & Durgin, 2015;Shaffer, McManama, Swank, Williams, & Durgin, 2014;Shaffer & Taylor, 2017). However, whereas the gains of free-hand or forearm measures are typically 1 for near surfaces and greater than 1 but less than the gains of verbal (over)estimates for geographical and ramp surfaces (i.e., steeper than the surface itself), the ladder placement was close to but shallower than the most stable position.…”
Section: Discussionsupporting
confidence: 82%